2001
DOI: 10.2134/jeq2001.303947x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Degradation Studies of Bentazone, Dichlorprop, MCPA, and Propiconazole in Norwegian Soils

Abstract: Laboratory degradation studies were performed in Norwegian soils using two commercial formulations (Tilt and Triagran-P) containing either propiconazole alone or a combination of bentazone, dichlorprop, and MCPA. These soils included a fine sandy loam from Hole and a loam from Kroer, both of which are representative of Norwegian agricultural soils. The third soil was a highly decomposed organic material from the Froland forest. A fourth soil from the Skuterud watershed was used only for propiconazole degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 27 publications
(33 reference statements)
3
36
2
Order By: Relevance
“…However, it has been observed that MCPA can be utilized by soil bacteria as a carbon source and converted to 4-chloro-2-methylphenol in the first step (Bollag et al 1967;Crespín et al 2001). The half-lives of MCPA for these two soils are similar to those reported in other studies (Torstensson et al 1975;Thorstensen and Lode 2001).…”
Section: Degradationsupporting
confidence: 88%
“…However, it has been observed that MCPA can be utilized by soil bacteria as a carbon source and converted to 4-chloro-2-methylphenol in the first step (Bollag et al 1967;Crespín et al 2001). The half-lives of MCPA for these two soils are similar to those reported in other studies (Torstensson et al 1975;Thorstensen and Lode 2001).…”
Section: Degradationsupporting
confidence: 88%
“…Such results were consistently obtained in three independent sets of soil column experiments with initial MCPA concentrations ranging from 15 to 50 mg g À1 dw (Figures 2 and 3a). Given extraction efficiencies of MCPA from soil 495% (see Materials and methods), the polarity of MCPA and the stability of MCPA in sterile soil (Thorstensen and Lode, 2001), disappearance of MCPA in soil is regarded as degradation further on. MCPA was not detected after 37 days of incubation ( Figure 3a) and in control soil without MCPA (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…However, Bromilow et al (1999) and Kim et al (2003) showed that mineralization of propiconazole was faster in sandy loam soil than the clay loam suggesting that due to lesser sorption of the fungicide in sandy loam soil than clay loam, the fungicide was more accessible to biological degradation. Thorestensen and Lode (2001) have reported that propiconazole degraded faster in soil with lower organic carbon content and its half life values in sandy loam (OC -1.4%) and loam (OC -2.5%) soils were 137 and 210 days, respectively.…”
Section: Resultsmentioning
confidence: 99%